(untitled) (Revista de Biología Marina y Oceanografía, 2022)
His most important contributions to scientific knowledge were in biological and physical oceanography of California and Humboldt Current systems. After retiring from IOC, in 2009 Patricio came back to Chile, where he became the Scientific Director of the Coastal and Ocean Program of CSIRO Australia-Chile. Finally, a cancer initially detected during his stay in California during the 1970’s, won the battle that Patricio fought with all his strength by accepting experimental medical treatments. In one of our last conversations held during June 2022, he told me that the treatment was showing “good signs” of success. He was wrong, and I have no more words to utter for such a splendid and irreplaceable scientist and friend.